2019
DOI: 10.3390/nu11092070
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Growth in Phenylketonuria: A Systematic Review and Meta-Analysis

Abstract: There is an ongoing debate regarding the impact of phenylketonuria (PKU) and its treatment on growth. To date, evidence from studies is inconsistent, and data on the whole developmental period is limited. The primary aim of this systematic review was to investigate the effects of a phenylalanine (Phe)-restricted diet on long-term growth in patients with PKU. Four electronic databases were searched for articles published until September 2018. A total of 887 results were found, but only 13 articles met eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 66 publications
(317 reference statements)
2
33
0
Order By: Relevance
“…Regarding physical development, no obvious differences were detected between the NBS and pre-NBS groups. Nevertheless, optimal growth outcomes were not attained in a previous study, even with advances in dietary treatments [ 23 ]. Although our study did not indicate major issues related to growth, physical development should be continuously evaluated for each individual with PKU.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding physical development, no obvious differences were detected between the NBS and pre-NBS groups. Nevertheless, optimal growth outcomes were not attained in a previous study, even with advances in dietary treatments [ 23 ]. Although our study did not indicate major issues related to growth, physical development should be continuously evaluated for each individual with PKU.…”
Section: Discussionmentioning
confidence: 95%
“…Another confounding factor that may affect body composition is the effect of a long-term low-phenylalanine diet higher in carbohydrates, which may be associated with a higher risk of adiposity and insulin resistance [ 45 , 46 ]. All of these factors may lead to under achievement of optimal growth potential in children with PKU [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional requirements of patients with HTI are currently not well defined, but higher protein intakes than WHO/FAO/UNU 2007 safe levels of protein intake are recommended [ 14 , 33 ], accounting for the known inefficient absorption of amino acids from protein substitutes [ 34 ]. In PKU, some studies have suggested that higher protein intakes are related to improved linear growth outcomes, although it is unclear which protein source (natural protein, protein equivalent from protein substitutes, or both) has the most influence on physical development [ 35 ]. In our cohort, median intakes (g/day) of prescribed total protein were correlated positively with height ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%